2008
DOI: 10.1038/ncb1816
|View full text |Cite
|
Sign up to set email alerts
|

An inducible autoregulatory loop between HIPK2 and Siah2 at the apex of the hypoxic response

Abstract: Oxygen deprivation (hypoxia) results in reprogrammed gene expression patterns that induce multifaceted cellular responses. Here we identify a regulated interaction between the serine/threonine kinase HIPK2 and the ubiquitin E3 ligase Siah2 as a mechanism controlling the hypoxic response. Under normoxic conditions, several mechanisms ensure HIPK2 stability: only a fraction of HIPK2 is found in association with Siah2, whereas HIPK2-mediated phosphorylation of this E3 ligase at positions 26, 28 and 68 weakens mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 25 publications
6
133
0
Order By: Relevance
“…In particular, we showed that this proapoptotic phenotype of MYCN-overexpressing cells also required p53 phosphorylation at serine 46 and were associated to a more pronounced activation of proapoptotic target genes compared with those involved in cell cycle arrest, such as the p21 WAF1 , in keeping with the current understanding of p53 activity (32,33). Among a few kinases able to phosphorylate p53 S46 , we focused our attention on HIPK2, a protein required for apoptosis induced by neurotrophin deprivation in developing sympathetic neurons (45), whose role in p53 S46 phosphorylation and p53-dependent apoptosis has clearly been established (26,36 (37)(38)(39)(40). DNA damage was shown to promote HIPK2 accumulation through an ATM/ATRdependent inhibition of its degradation by Siah1 and/or WSB1 ubiquitin ligases (38,40).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In particular, we showed that this proapoptotic phenotype of MYCN-overexpressing cells also required p53 phosphorylation at serine 46 and were associated to a more pronounced activation of proapoptotic target genes compared with those involved in cell cycle arrest, such as the p21 WAF1 , in keeping with the current understanding of p53 activity (32,33). Among a few kinases able to phosphorylate p53 S46 , we focused our attention on HIPK2, a protein required for apoptosis induced by neurotrophin deprivation in developing sympathetic neurons (45), whose role in p53 S46 phosphorylation and p53-dependent apoptosis has clearly been established (26,36 (37)(38)(39)(40). DNA damage was shown to promote HIPK2 accumulation through an ATM/ATRdependent inhibition of its degradation by Siah1 and/or WSB1 ubiquitin ligases (38,40).…”
Section: Discussionmentioning
confidence: 75%
“…3D), suggesting that HIPK2 induction by MYCN might occur at the level of protein stability. HIPK2 expression is largely controlled via proteasomal degradation by several E3 ubiquitin ligases (37)(38)(39)(40). Importantly, in response to DNA damage, the ATM and ATR kinases were shown to promote HIPK2 accumulation by inhibiting its ubiquitin ligases Siah1 and WSB1 (38,40).…”
Section: Sensitization To Apoptosis By Mycn Is Linked To P53 S46 Phosmentioning
confidence: 99%
“…Siah-2 and HIPK2 show a mutual regulation including HIPK2-mediated Siah-2 phosphorylation at positions 26, 28 and 68, which weakens mutual binding between both the proteins and destabilizes its phosphorylated interaction partner. Hypoxic condition triggers increased HIPK2/ Siah-2 interaction, which occurs by a still unknown mechanism but that induces HIPK2 polyubiquitination (Calzado et al, 2009a). Accordingly, hypoxia-induced HIPK2 elimination is markedly reduced in Siah-2-deficient cells.…”
Section: Hipk2 Inactivation In Tumors and P53 Dysfunctionmentioning
confidence: 99%
“…HIPK2 is downregulated by RING family ligase seven in absentia homolog-2 (Siah2) during hypoxia (Calzado et al, 2009a). Siah-2 and HIPK2 show a mutual regulation including HIPK2-mediated Siah-2 phosphorylation at positions 26, 28 and 68, which weakens mutual binding between both the proteins and destabilizes its phosphorylated interaction partner.…”
Section: Hipk2 Inactivation In Tumors and P53 Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation